Strontium isotope studies of sedimentary rocks - Bath, A (1974)
The present investigation has been undertaken in an attempt to clarify the effects of hte physico-chemical conditions encountered during burial diagenesis and very low-grade metamorphism on the Rb-Sr systems of the various components of argillaceous sediments. Two methods of study have been used: 9a) comparison of Rb-Sr data from suites of variably metamorphosed argillites, and (b) an investigation of the mobility of Rb and Sr in a clay-water system under metamorphic conditions simulated in teh laboratory. A suite of Lower Silurian (Upper Llandovery) mudstones (clay fraction consisting of mixed-layer illite-smectite+kaolinite) gives whole-rock RbSr isotope date which form a non-linear array on an isochron diagram. A best-fit line through all data points represents an age of ca. 510 m.y., which may be compared with an estimate of ca. 420 m.y. for the true stratigraphic age. This is interpreted as reflecting the multi-component nature of the sediment, the components ranging from detrital minerals (e.g. kaolinite and possibly illite) and partially transformed mixed-layer minerals, to authigenic phases (e.g. calcite). This interpretation is amplified by data from within-sample size-fractions, whose Rb-Sr model ages decrease towards the estimated age of deposition as the grain size decreases. [Please see the pdf to read the rest of the abstract]